Silbermann’s “Revue entomologique”: Publication Dates for Nomenclatural Purposes and Bibliographic Notes (Insecta, mainly Coleoptera) - Nagel, Peter; Schmidlin, Lara (Zootaxa, 2014)
The rare yet entomologically important scientific journal “Revue entomologique” was published in French language in five volumes during the first half of the nineteenth century. We provide some bibliographic notes which reveal, for example, the motivation and goals of the editor, Gustave Silbermann. He wanted to contribute to an exchange of entomological knowledge between French and German scientists, in particular by translating German articles into French and to inform his readers of new German and French entomological literature. The work deals with many taxa, mainly beetles, yet also moths, cicadas and other insects. The journal contains taxonomic notes and species descriptions for which correct dating is essential. Evidence inside the books indicates the partly wrong assignment of the publication dates printed on the title pages from 1833 to 1837. We found one depository holding the originally assembled and unbound fascicles of the first two volumes. Despite the month of publication being absent on all wrappers, their original composition allowed the detailed reconstruction of publication dates, as well as of unpaginated species descriptions. We analysed the work, attributed page numbers to single or merged fascicles and provided publication dates for all 30 fascicles, which were shown to have been published from 1833 to 1840. We also traced the enigmatic reference for the description of a longhorn beetle (Molorchus ulmi Chevrolat, 1838) and were able to demonstrate that its supposed association with the “Revue entomologique” is erroneous.